Pendidikan Luar Sekolah; Kajian Optimalisasi Fungsi Keluarga sebagai Bagian Institusi Pendidikan - Muhammad Asrori Ma'sum (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2015)
Education plays an important role in the Islamic world. Conception of lifelong education already existed long before the birth of the concept of Education Outside School. This conception is not hierarchical, but rather an educational process conducted since the period of alastu birabbikum. (period in the womb) to the period yurfa’ûn (the period when humans resurrected). Because the education lasts a lifetime, then the process can be done in families, communities, institutions of formal and non-formal. Public response to what is happening outside school, both within the family and in a social environment or community, is not regarded as an educational process, it becomes a separate problem, which is on that account that needs to be studied to be placed in their respective positions.